Knowledge, Availability of Facilities and Family Support in Implementing Health Protocols After Covid-19 Vaccination - Djara Liwe, Deslyn; Keraf, Marselino Kharitas Purna Abdi; Ndoen, Enjelita Mariance (Journal of Health and Behavioral Science, 2023)
Along with the Covid-19 vaccination, the public is encouraged to continue to apply health protocols. Individuals who have been vaccinated still have a risk of contracting Covid-19. This study analyzed the correlation of knowledge, the availability of facilities, and family support with the application of health protocols after Covid-19 vaccination among FKM students. The research used analytic observational with a cross-sectional approach and 296 students as the research sample, obtained with a stratified random sampling technique. The results showed that there was a correlation between knowledge (p 0.000), availability of facilities (p = 0.000), and family support (p = 0.000) with the implementation of post-Covid-19 vaccination health protocols for FKM students. FKM students should be good role models and use different ways of health promotion to raise the public’s awareness of the significance of health protocol implementation after the Covid-19 vaccination.